Detection and path prediction of aircraft based on acoustics and vibration. (2020) - Sakthivel, C.; Sureshkumar, B.; Ramkumar, R.; Yokeswaran, R.
Abstract: Detection of UAV or aircraft by radar technology in low altitude is difficult due to its low radar cross section. A method of recognition and detection of UAV or aircraft using low cost ground based acoustic and vibration sensor is proposed here. This work done by integrating and establishing these sensors in a desirable location such as country's line of control (LOC). Concentrating on the nonlinear trajectory of an acoustic and vibrational source, the future positions can be predicted by using Particle filter. Multipath time delay estimation technique is used to find the altitude of the source.